Exploring Communication Process At Virtual Organization On “Campaign.Com” From Upward Downward Horizontal And Diagonal Flow Aspect - Larasati, Sheila Tirtaningrum; Suharti, Lieli (UNIVERSITAS PAKUAN, 2022)
The aim of this study is to analyze the communication processes that flow up, down, horizontally, and diagonally on Campaign.com in order to identify the reasons for communication process barriers and solutions for how to solve problems. This study employs a qualitative research methodology that combines descriptive and exploratory research methodologies. Semi-structured interviews conducted via Internet communication channels were used to obtain data. Three Campaign.com employees participated in this study. This research concluded that the communication process on Campaign.com, which depends on online communication media such as Slack, E-mail, G-Meet, and WhatsApp, is running well, but less effectively. Campaign.com employees communicate about their work or tasks upwards, downwards, horizontally, and diagonally, together with personal check-ins and talking to encourage employee connection. Campaign.com employees frequently experience communication problems as a result of ineffective communication. Nonetheless, Campaign.com employees understand what is causing the obstacles they are experiencing and have strategies prepared for solving problems. As a result, less effective communication may be conquered and a better communication process can be developed.